The effectiveness of inclined mats on elementary school students' self-confidence levels - Sujiasno, Hendri; Kristyandaru, Advendi; Febriyanti, Irma; Yuer, Wang (Universitas Tanjungpura, 2026)
Background. Floor gymnastics activities in elementary school physical education often present psychological barriers for students, particularly fear of falling or injury when performing backward roll movements. These conditions may reduce participation and limit the development of students’ self-confidence during learning. The use of supportive learning media is therefore needed to create a safer and more conducive learning environment. Objectives. This study aimed to examine the effectiveness of inclined plane mats in improving the self-confidence of elementary school students during backward roll learning in Physical Education, Sports, and Health. Methods. This study employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. The participants were 52 fifth-grade students of SD IIS PSM Magetan in the 2025/2026 academic year. Students’ self-confidence was measured using a Likert-scale questionnaire administered before and after the learning intervention. The intervention consisted of structured backward roll practice using inclined plane mats over several learning sessions. Data were analyzed using descriptive statistics and a paired sample t-test with a significance level of 0.05. Results. The findings indicated a significant increase in students’ self-confidence after the intervention. The average self-confidence score improved from the pretest to the posttest, and statistical analysis showed a significant difference (p < 0.05). The inclined plane mat helped reduce students’ fear during movement practice and provided a safer learning experience. Conclusion. The use of inclined plane mats is effective in enhancing elementary school students’ self-confidence in backward roll learning. The findings highlight the importance of adaptive learning media in creating safe, supportive, and confidence-building environments in physical education.